Survey of U.S. Boards That Review Mental Health–Related Research - Catania, Joseph A. (2008)
We obtained data on Institutional Review Boards (IRBs) that review mental health–related applications (MHRAs) in a national survey of institutions with federally assured human research protection programs. Approximately 57% of IRBs review MHRAs, and among these a small percentage may not have mental health experts on their committees (5%). Moreover, mental health experts on IRB committees at high research volume institutions are carrying substantially greater workloads than their lower volume counterparts. In terms of committee demographics, more women (36%) are serving as IRB Chairs on committees that review MHRAs than expected from their representation on medical or university faculties; ethnic minority faculty have lower representation among Chairs than might be expected from their overall faculty representation. Our findings suggest the need for additional studies to (a) examine if the number of mental health experts on IRBs should be increased particularly among IRBs reviewing a high volume of MHRAs, (b) determine if the breadth of expertise among IRB mental health experts corresponds to the range of substantive and methodological approaches represented by the mental health protocols under review, and (c) examine if recruiting IRB scientific expertise from outside an institution, a more common practice among smaller research entities, impacts review quality.